Tamadun prasejarah Malaysia, Muzium Negara = Prehistoric civilisation of Malaysia, National Museum - Adi Taha; Malaysia. Kementerian Perpaduan, Kebudayaan, Kesenian dan Warisan. Jabatan Muzium Malaysia (Kuala Lumpur : Jabatan Muzium Malaysia, 2011)
Includes bibliographical references and index